Investigating K/π Decay Muon Yields Using K/π Yields and a Fast Simulation Method - Zuman Zhang; Sha Li; Ning Yu; Hongge Xu; Yuanmeng Xiong; Kun Liu (Particles, 2025)
In ultra-relativistic heavy-ion collisions, the study of muons from kaon (K) and pion (<semantics>π</semantics>) decays provides insights into hadron production and propagation in the Quark–Gluon Plasma (QGP). This paper investigates muon yields from K and <semantics>π</semantics> decays in Pb–Pb collisions at <semantics><msqrt>sNN</msqrt>=2.76</semantics> TeV using a fast simulation method. We employ a fast Monte Carlo procedure to estimate muon yields from charged kaons and pions. The simulation involves generating pions and kaons with uniform <semantics>pT</semantics> and y distributions, simulating their decay kinematics via PYTHIA, and reweighting to match the physical spectra. Our results show the transverse momentum distributions of muons from K and <semantics>π</semantics> decays at forward rapidity (<semantics>2.5<y<4.0</semantics>) for different centrality classes. The systematic uncertainties are primarily from the mid-rapidity charged K/<semantics>π</semantics> spectra and rapidity-dependent <semantics>RAA</semantics> uncertainties. The muon yields from pion and kaon decays exhibit consistency across centrality classes in the <semantics>pT</semantics> range of 3–10 GeV/c. This study contributes to understanding hadronic interactions and decay kinematics in heavy-ion collisions, offering references for investigating pion and kaon decay channels and hot medium effects.